Production Layout Improvement for Steel Fabrication Works - N. M. Zuki, N. M.; M. F. F., Ab Rashid; A. N., Mohd Rose; Woh, Yu Ting (2014)

(untitled)
This paper focuses on the study of a steel fabrication works production line in a particular company in Malaysia. The company’s main business is steel cutting and bending service. Due to high number of customer orders, the current production layout has to be improved. The objectives of the study was to improve the current layout in order to minimise material handling cost, improve flexibility for operation, utilise the available area and minimise overall production time. The improvement process layout was studied using WITNESS software. Production analysis has been conducted in the process flow of the company in order to identify improvement at the problematic areas. Finally, improvement alternative solutions were proposed based on Witness simulation.